American literature in Studia Anglica Posnaniensia 1968-2008. A selection of articles. Janusz Semrau (ed.) - Stachura, Paweł (Studia Anglica Posnaniensia, 2010)
Review: American literature in Studia Anglica Posnaniensia 1968-2008. A selection of articles. Janusz Semrau (ed.). Poznań: Wydawnictwo Naukowe UAM, 2009. Pp. 333.